'A judicious and industrious compiler': Mapping Postlethwayt's Dictionary of Commerce. Issue 6 (2nd November 2017) - van den Berg, Richard
ABSTRACT: This paper takes as its guide the largest compilation of commercial knowledge of the mid-eighteenth century in the English language, Malachy Postlethwayt's Universal Dictionary of Trade and Commerce (1751–1755). Using network analysis, the many cross-references between entries in this work allow one to identify clusters of themes and literatures within the mass of materials. Pictures are presented that can be interpreted as 'mind maps' grouping the commercial literature by various topics and themes. The paper then focuses on one novel aspect of Postlethwayt's work, i.e., his inclusion besides entries on 'practical' topics of 'political' discussions, and identifies his sources.